Persistent plasticizers and bisphenol in the cheese of Tunisian markets induced biochemical and histopathological alterations in male BALB/c mice - Beltifa, Asma; Feriani, Anouar; Macherki, Monia; Ghorbel, Asma; Ghazouani, Lakhdar; Di Bella, Giuseppa; Sire, Olivier; Van Loco, Joris; Reyns, Tim; Mansour, Hedi Ben (Environmental science and pollution research international, 2018)
Clinical evidences, experimental models, and epidemiology of many studies suggest that phthalate-based plasticizers , aliphatic ester , and bisphenol A (BPA) have major risks for humans by targeting different organs and body systems. The current study has been designed firstly to analyze three categories of cheese with and without their exposure to the sun and packed in packages with an inner surface plastic-covered film in order to identify the dibutyl phthalate (DBP); benzyl butyl phthalate (BBP); bis(2-ethylhexyl) phthalate (DEHP); diisodecyl phthalate (DiDP); diisononyl phthalate (DiNP); and 1,2-cyclohexane dicarboxylic acid diisononyl ester (DINCH) by GC-MS/MS, except for the bisphenol A, which is by UPLC-MS/MS, and secondly to assess the toxicity of the identified chemical molecules and cheese samples on the liver and kidney of mice. Our results showed that the cheese contains high quantities of DBP and DEHP with the concentrations up to 0.46 and 2.339 mg/kg, respectively. Other types of cheese, such as rolled and triangular cheeses, contain little quantities of the all substances at concentrations below the standard limits. In vivo, the obtained data clearly demonstrated that the acute administration of DBP, DEHP, and the tested cheese significantly induced liver and kidney injuries in mice manifested by a rise in plasma alanine aminotransferase, aspartate aminotransferase, blood urea nitrogen, lactate dehydrogenase, urea, creatinine, and uric acid when compared with control animals. In addition, the histopathological study confirmed the perturbation of biochemical parameters and showed that the hepatic and renal structures were altered. Indeed, the hepatotoxic and nephrotoxic effects are more pronounced when cheese was exposed to the sun.